Process and Assessment Standards In Current Practice Curriculum at Universitas Muhammadiyah Bogor - Srinawati, Wawat; Susianto, Tri Endar; Ambartiasari, Geta; Ichsan, Ichsan; Daud, Muslem (UNIVERSITAS SERAMBI MEKKAH, 2023)
The aim of the research are assessment tasks to have an impact on student learning, it is critical that students have a clear perspective of the primary purpose of each task and how their responses will be interpreted and rewarded. This research method using the current terms diagnostic, formative and summative to describe many of the traditional aspects associated with current assessment prac-tice and introduces the term integrative assessment to specifically describe tasks whose primary purpose is to influence students approaches to future learning by providing activities that define and track strategies that students use to assess their own learning abilities and problem-solving capabilities, the quality and standards of student responses and how students might adapt their learning to future scenarios. The Results of the research study show integrated and integrative assessment have been used previously in the literature to describe a range of activities, including an appropriate balance between assessment for learning and assessment of learning; for various aspects of coherence and alignment between learning objectives and their associated assessment tasks; and for monitoring the efficacy of assessments in enhancing different types of learning.